2005
DOI: 10.1021/jf050802j
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone Conjugates Are Underestimated in Tissues Using Enzymatic Hydrolysis

Abstract: Many health effects of soy foods are attributed to isoflavones. Isoflavones upon absorption present as free form, glucuronide, and sulfate conjugates in blood, urine, and bile. Little is known about the molecular forms and the relative concentrations of soy isoflavones in target organs. Acid hydrolysis or enzymatic hydrolysis (glucuronidases and sulfatases) was used to study isoflavone contents in the heart, brain, epididymis, fat, lung, testis, liver, pituitary gland, prostate gland, mammary glands, uterus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…They were largely present as glucurono and/or sulphoconjugate forms [35,36]. A methylated derivative of quercetin (isorhamnetin) was also reported as the main metabolite in testes of quercetin-fed rats [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were largely present as glucurono and/or sulphoconjugate forms [35,36]. A methylated derivative of quercetin (isorhamnetin) was also reported as the main metabolite in testes of quercetin-fed rats [38].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids such as isoflavones and quercetin have been identified in testes from rats fed flavonoid-enriched diets [35,36,38]. They were largely present as glucurono and/or sulphoconjugate forms [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, a separate incubation of a commercially obtainable substrate (for example 4-methylumbelliferone glucuronide) in the same matrix is used to monitor the -glucuronidase activity (Blount, Milgram et al 2000). Each incubation should contain 200 -25 000 units of -glucuronidase per 1 mL of incubation medium (Gu, Laly et al 2005;Belanger, Caron et al 2009). Note that vendors define the glucuronidase activity in Roy or in Fishman units, where 1 Fishman unit releases 1 µg phenolphthalein from phenolphthalein-β-glucuronide in 1 h at 38°C.…”
Section: Sample Incubationmentioning
confidence: 99%
“…Alternatively, tissue:blood partition coefficients can also be obtained using in silico methods based on octanol-water partition coefficient [60]. Kinetic parameters for ADME can be obtained using 1) experimental in vitro models using primary cell cultures, cells from cell lines in culture, subcellular fractions, tissue slices, or relevant recombinants enzymes of organs [61,62], 2) available in silico methods [63][64][65], or 3) by fitting the model to available in vivo data [66].…”
Section: Pbk Modelsmentioning
confidence: 99%
“…In most studies, flavonoid conjugates in plasma were identified and quantified from the amounts of aglycone liberated from conjugated metabolites by using β-glucuronidase and sulfatase to deconjugate the conjugated metabolites to their respective aglycone [60][61][62][63][64][65][66][67][68]. This method has been criticized for running a risk of underestimation and lack of information on the absolute structural conformation of flavonoid conjugates especially with respect to the conjugation position [60,61]. The use of advanced analytical methods in chromatography and mass spectrometry can also not provide the absolute conformation of the chemical structure of individual flavonoid conjugates [69].…”
Section: Quality Of In Vivo Data On Metabolic Patterns In Plasma For mentioning
confidence: 99%